CYBERCOUNSELING FOR GENERATION Z: OPPORTUNITIES, CHALLENGES, AND RECOMMENDATIONS - Agustin Andhika Putri; Angelia Astri Hermatika (EDUCATIONE, 2026)
Digital technology and the internet are developing rapidly due to advances in science and technology. The development of the internet has had a positive impact on various mental health services in Indonesia. Cybercounseling is a new innovation in the world of counseling. Cybercounseling is an online counseling service that can be accessed anywhere by its users. The purpose of this study is to discuss the application and challenges of cybercounseling in Indonesia. This study uses a literature review method, analyzing 15 selected articles from an initial pool of 50 articles obtained through multiple databases, using keywords such as “cybercounseling,” “online counseling,” and “Generation Z.” The selection of articles focused on relevance to the development, opportunities, challenges, and recommendations for digital counseling. The findings suggest that cybercounseling aligns with the digital preferences of Generation Z, as its anonymity, accessibility, and flexibility facilitate engagement and reduce barriers to seeking support. However, its effectiveness is constrained by unresolved issues, particularly ethical standards, data security, and confidentiality, highlighting a gap between technological adoption and regulatory readiness. These challenges suggest that successful implementation depends not only on technological availability but also on clear governance and professional preparedness. In conclusion, the literature indicates that cybercounseling is a promising innovation for expanding mental health support for Generation Z in Indonesia. Nevertheless, realizing its potential requires strengthened regulations, reliable infrastructure, and continuous development of counselors’ digital competencies. Addressing these factors is essential to ensure that cybercounseling services are effective, ethical, and responsive to the needs of a digitally connected generation in the Society 5.0 era.